TINJAUAN TERHADAP FAKTOR INTERNAL PERUSAHAAN YANG MEMPENGARUHI FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Dwi Astuti; Shinta Permata Sari (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
Financial distress is an indication that the company is in financial difficulties. This condition also occurs in banking companies, given the recent pandemic conditions that are disrupted the company's operational activities. Therefore, the company can take preventive measures by having attention to the health performance of the bank using financial ratios. This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Return on Assets (ROA), Return on Equity (ROE), and Operational Costs and Income (BOPO) on financial distress. The population in this study are banking companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Sampling is collected using the purposive sampling technique and obtained from 40 banking companies that meet the criteria. Data are analyzed using multiple linear regression. In this study, the result shows that Capital Adequacy Ratio and Operational Costs and Income have an effect on financial distress. Meanwhile, Non-Performing Loans, Return on Assets, and Return on Equity has no effect on financial distress.